2020
DOI: 10.1186/s41983-020-00173-4
|View full text |Cite
|
Sign up to set email alerts
|

Magnitude, risk factors and outcomes of stroke at Debre Markos Referral Hospital, Northwest Ethiopia: a retrospective observational study

Abstract: Background Stroke is one of the leading causes of death and disability in developing countries. The burden of stroke has varied widely in different areas, and there is a paucity of information about stroke in the selected study area. Objectives To assess the burden, risk factors, and outcomes of stroke at Debre Markos Referral Hospital, Northwest Ethiopia Patients and methods A hospital-based retrospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
30
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 42 publications
8
30
3
1
Order By: Relevance
“…In this study, the overall incidence of stroke was 3.15% and the rate was lower than the report of different studies conducted in Ethiopia like 19.3%, 21 7.7%, 22 7.5%, 23 and 7.2%. 24 Lack of the diagnostic technology such as MRI or CT scan and manual registration and management system of records in the study hospital might have an association with lower rates of stroke patients.…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…In this study, the overall incidence of stroke was 3.15% and the rate was lower than the report of different studies conducted in Ethiopia like 19.3%, 21 7.7%, 22 7.5%, 23 and 7.2%. 24 Lack of the diagnostic technology such as MRI or CT scan and manual registration and management system of records in the study hospital might have an association with lower rates of stroke patients.…”
Section: Discussioncontrasting
confidence: 71%
“…Likewise, several studies reported that ischemic stroke was the dominant subtype of stroke. 21 24 , 26 , 27 , 29 33 However, some studies reported that hemorrhagic stroke is the dominant subtype of the stroke in other parts of Ethiopia. 12 , 25 , 12 Patients in this study were more likely to have risk factors associated with ischemic stroke and this might be a reason for the variation.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 21 , 24 , 34 The sample size of the included studies was ranged from 36 to 1054. 13 , 36 Of the total studies, most of them (15 studies) were conducted in Eastern Africa 15 , 16 , 19 , 20 , 22 24 , 26 29 , 31 , 32 , 34 , 37 and eight of them were in Western Africa 12 14 , 21 , 30 , 33 , 35 , 36 and the remaining four studies were conducted in Southern Africa 11 , 17 , 18 , 25 ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“… 8 , 10 Several studies were conducted to evaluate the in-hospital mortality rate from acute stroke in sub-Saharan Africa. 11 37 However, the mortality rate has not been summarized to reflect the overall in-hospital mortality rate in the region. Hence, this systematic review and meta-analysis aimed to obtain more robust evidence on stroke treatment outcomes from the existing literature in sub-Saharan Africa countries.…”
Section: Introductionmentioning
confidence: 99%
“…Though hypertension is the main reported risk factor of stroke among the included studies, the proportion of hypertension among stroke patients found in the current study is lower than previous studies conducted in India, Bosnia-Herzegovina, Zambia, Nigeria, Malawi, and Bangladesh [ 33 38 ]. The possible explanation for this variation might be due to the lack of diagnostic modalities and proficiency [ 39 ]. Additionally, this could be due to the included studies measured hypertension in the medical record prior to the occurrence of stroke [ 22 ].…”
Section: Discussionmentioning
confidence: 99%